Formation of Tumorspheres with Increased Stemness without External Mitogens in a Lung Cancer Model. (6th January 2016) - Yakisich, Juan Sebastian; Azad, Neelam; Venkatadri, Rajkumar; Kulkarni, Yogesh; Wright, Clayton; Kaushik, Vivek; Iyer, Anand Krishnan V.
Abstract : Like with most solid tumors, the presence of a subpopulation of cancer stem cells (CSCs) or cancer stem-like cells (CS-LCs) has been associated with chemoresistance and tumor relapse in lung cancer cells. In the absence of serum, CSCs/CS-LCs have the ability to grow as lung tumorspheres (LTSs), and this system is routinely used for isolation and characterization of putative CSCs/CS-LCs. Methods to isolate LTSs are usually performed in serum-free media supplemented with specific additives such as epidermal growth factor and basic fibroblast growth factor. In this study, we report the generation of LTSs without the addition of any external mitogenic stimulation. LTSs generated in this manner demonstrated several traits usually associated with increased stemness such as elevated expression of the stemness-associated marker Sox2 and increased chemoresistance to conventional anticancer drugs. In addition, we report that the FDA-approved drug Digitoxin, at concentration close to its therapeutic level, decreased the viability of LTSs and downregulated Sox2 independent of the PI3K/AKT pathway. The potential use of LTSs generated without the addition of any external mitogenic stimulation to study the role of specific factor(s) associated with stemness properties is also discussed.